Peripheral blood buffy coat smear: a promising tool for diagnosis of visceral leishmaniasis - Salam, Md. Abdus; Khan, Md. Gulam Musawwir; Bhaskar, Khondaker Rifat Hasan; Afrad, Mokibul Hassan; Huda, M. Mamun; Mondal, Dinesh (American Society for Microbiology, 2012)
Confirmative diagnosis of visceral leishmaniasis (VL) is still a challenge at the primary health care facilities in most of the rural areas of endemicity in the Indian subcontinent. Conventional methods for parasitological confirmation are risky and require skilled personnel, and hence they are unavailable to the poor people in the regions of endemicity. Buffy coat smear microscopy, as a minimally invasive, simple alternative for the parasitological diagnosis of VL, was evaluated in this prospective study. One hundred twelve VL patients were enrolled in this study. The buffy coat was separated from peripheral blood of all enrolled subjects using Histopaque-1119 solution. Leishman-stained buffy coat smears were examined for Leishmania donovani bodies, and buffy coat was also utilized for detection of parasite DNA by Leishmania nested PCR (LnPCR) for all cases. Concomitant splenic smears could be examined for L. donovani bodies in 66 cases, and the parasite load was graded on a scale of 1to 6for L. donovani-positive smears. All splenic smear-positive cases were also found to be positive by LnPCR. Of 112 enrolled VL cases, 103 (92%) were found to be positive for L. donovani bodies in buffy coat smear microscopy, which is promising as a confirmative diagnosis tool. We have also found a significant association of the buffy coat smear positivity with parasitic burden in the spleen smear. In this preliminary observation in Bangladesh, buffy coat smear microscopy has been found to be very simple, minimally invasive, and risk-free method of parasitological diagnosis of VL with a good diagnostic accuracy and potential for field use.